THE RELATIONSHIP OF RISK PERCEPTION AND INTEREST OF UIN ALAUDDIN MAKASSAR STUDENTS IN USING APPLICATION-BASED TELEMEDICINE SERVICES - Surahmawati,; Yudi Adnan,; Royyanintias,; Syarfaini,; Nur Rahmah, (Homes Journal: Hospital Management Studies Journal, 2024)
Backround : Applications that offer healthcare services remotely between doctors and patients are known as telemedicine. Initial survey results show that there are still students who have never used telemedicine. Objective: This study aims to see how students' risk perceptions relate to their interest in using telemedicine services. Methods: This study uses a cross-sectional approach. In this study, 213 people were randomly selected from the sample group based on the year of the student's class. This research instrument is a questionnaire consisting of offline and online questionnaires (Google Forms). This study was conducted from 10 July to 21 August 2023. Data analysis used consisted of univariate tests using the frequency distribution and bivariate tests using the chi-square. Result: Most students have used telemedicine. The most widely used application is the Halodoc application. The results of the chi-square test show that the p-value is 0.079, which is a value greater than 0.05 with an OR value of 2.091. Conclusion: This indicates that there is no relationship between students' risk perceptions and their willingness to use telemedicine services. Research on telemedicine needs to be carried out in depth and also try new approaches